1998
DOI: 10.1038/sj.onc.1201654
|View full text |Cite
|
Sign up to set email alerts
|

Physical map of the D6S149-D6S193 region on chromosome 6Q27 and its involement in benign surface epithelial ovarian tumours

Abstract: A detailed long range restriction map of the region de®ned by markers D6S149 and D6S193 on chromosome 6q27 has been constructed. This was achieved by YAC cloning and contig assembling of the same region. Seven YAC clones were found to span the almost 1000 Kb region¯anked by the two markers which on the genetic map resulted to be 1.9 cM apart. With some of the characterized YAC clones we undertook a molecular cytogenetic analysis of 20 benign ovarian tumors. The rationale for this was the recent mapping to a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…This was supported by FISH studies performed directly on metaphase spreads from ovarian tumours using YACs (Tibiletti et al, 1996(Tibiletti et al, , 1998. Precise delineation of the minimal interval of allele loss was shown to be between D6S264 and D6S297 by us previously, which overlapped with that between D6S193 and D6S149 (Saito et al, 1992).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This was supported by FISH studies performed directly on metaphase spreads from ovarian tumours using YACs (Tibiletti et al, 1996(Tibiletti et al, , 1998. Precise delineation of the minimal interval of allele loss was shown to be between D6S264 and D6S297 by us previously, which overlapped with that between D6S193 and D6S149 (Saito et al, 1992).…”
Section: Discussionsupporting
confidence: 55%
“…Further evidence that there might be a putative tumour suppressor gene around D6S193 is provided by FISH studies using YACs on direct metaphase spreads from fresh ovarian tumours which suggested that this change might be important even in early ovarian tumours (Tibiletti et al, 1996(Tibiletti et al, , 1998. It has also been shown that the same region is implicated in a subset of lymphomas and breast cancer (Gaidano et al, 1992;Menasce et al, 1994;Rodriguez et al, 2000;Tibiletti et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that another locus within 6q21-q23 also harbors a gene functioning as tumor suppressor for ovarian carcinoma cannot be ruled out. Indeed, the current evidence suggests that chromosome 6 contains several tumor suppressor genes important in these tumors (Banga et al, 1997;Cooke et al, 1996;Foulkes et al, 1993;Orphanos et al, 1995;Saha et al, 1995;Saito et al, 1992Saito et al, , 1996Tibiletti et al, 1998;Wan et al, 1994). More recently, Sandhu et al (1996) provided functional evidence for another candidate region on chromosome 6q important in ovarian tumorigenesis.…”
Section: Discussionmentioning
confidence: 96%
“…This was further confirmed by examination of another panel of tumours (ChenevixTrench et al, 1997). Further evidence of a putative tumour suppressor gene located near the marker D6S193 was suggested by fluorescent in situ hybridization studies using yeast artificial chromosome (YACs) on direct metaphase spreads from fresh ovarian tumours that demonstrated that this change might be important even in early ovarian tumours (Tibiletti et al, 1996(Tibiletti et al, , 1998(Tibiletti et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%